Blood donors implicated in transfusion‐related acute lung injury with patient‐specific HLA antibodies are more broadly sensitized to HLA antigens compared to other blood donors. Issue 3 (28th June 2012) - Saw, Chee‐Loong; Hannach, Barbara; Petrazsko, Tanya; Nickerson, Peter
<x xml:space="preserve">Abstract</x> BACKGROUND: The prevalence of HLA antibodies in randomly surveyed blood donors was compared to the prevalence of antibody in donors who were associated with transfusion‐related acute lung injury (TRALI) cases reported to Canadian Blood Services (CBS). STUDY DESIGN AND METHODS: Current operating procedure mandates that the CBS TRALI Medical Review Group (TMRG) refer possible TRALI cases to the (CBS) Platelet Immunology Laboratory for investigation. Donor samples from these TRALI cases were screened for HLA antibodies. In parallel, a survey was conducted to screen serum samples from blood donors who were not associated in TRALI cases. A comparison analysis of HLA antibody profiles in the two groups of donors was performed. RESULTS: We studied 121 TRALI‐associated donors (TDs) who were recalled in a total of 44 cases reported to CBS and classified by TMRG. We also studied 149 survey donors (SDs) who were deferred for donation for varied reasons and consented to participate in a survey for HLA antibody screening. Twenty‐two percent of SDs and 50.4% of TDs tested positive for HLA antibodies. In addition, TDs who were implicated in TRALI demonstrated broader sensitization and higher level of quantitative HLA antibody compared to nonimplicated TDs and SDs. CONCLUSION: Patient‐specific Class I and II HLA antibodies are directly related to the risk of TRALI. Moreover, it supports the concept that HLA antibody strength is directly related to the risk of TRALI when the HLA antibody is patient specific; however, no clear cutoff as defined by mean fluorescence intensity is evident.